Science Teachers' Experiences when Implementing Problem-based Learning in Rural Schools. Issue 2 (4th May 2021) - Osman, Ali; Kriek, Jeanne
Abstract : Problem-based learning (PBL) is considered to be an effective teaching and learning strategy as it leads to longer retention of concepts learnt, improves problem-solving skills and enhances critical thinking. However, teachers often find it difficult to implement as they do not receive guidance during their initial training. A professional development intervention lasting four weekends was organised on developing rural science teachers' knowledge and skills in the use of PBL strategies for teaching circuit electricity. The aim of the study was firstly to explore how rural science teachers' knowledge and classroom activity change after the intervention and secondly to establish these teachers' experiences when implementing the strategy in rural schools. Three different instruments, i.e. open-ended questionnaires, interview schedules and a lesson observation protocol, were used to obtain qualitative data from 16 teachers in a total of eight purposively selected schools. The theoretical framework used was the social constructivist theory as it embeds the PBL strategy. Findings indicate that teachers indeed changed their teaching as learners made predictions, formulated hypotheses and were involved in thought-provoking activities. Rural teachers' experiences were similar to previous findings. However, these rural teachers had to additionally deal with the challenge of large classes and a lack of information technology support in the use of a PBL strategy. The divergence of the language of learning and teaching from the learners' home language was not found to be problematic. Not all teachers were qualified but according to the classroom observations they all displayed good content knowledge in circuit electricity, even when using PBL strategies.